Comment on "Hole-pinned defect-dipoles induced colossal permittivity in Bi doped SrTiO3 ceramics with Sr deficiency". (28th February 2021) - Tkach, Alexander; Okhay, Olena
Abstract: With this contribution, as a comment to the publication in Journal of Materials Science & Technology 44 (2020) 54, reporting giant dielectric response, structural characterization and numerical simulations in Sr1-1.5 x Bi x TiO3 ceramics, we show that the reported results are rather contradicting and not well analysed, while the suggested mechanism for the giant permittivity response is not valid or doubtful and has to be reconsidered. Moreover, many details and data are missing making impossible not only to call the obtained results very suitable for practical application but even to reproduce them.